Pengembangan Media Pembelajaran Berbasis IT dalam Pembelajaran PAI PAUD pada Era Society 5.0 - Cahyono, Budi; Fauzi, Fauzi (Jurnal Kependidikan, 2021)
Islamic religious learning for early childhood is increasingly prioritized at this time. Parents are required to introduce their children to the teachings of Islam from an early age so that knowledge, insight, and monotheism will be more attached and leave an imprint on the child's heart. At the stage of early childhood education, the child will tend to be more interested in learning media that is easy to understand and includes moving animated images and sounds that attract attention. With IT-based media in delivering teaching materials and students can carry out their activities directly by interacting via computers, laptops and Android phones. For this reason, an interactive learning media application was made to introduce Islam by using one of the applicative programming. So that it helps teachers or parents to easily introduce Islam with a pleasant appearance so that the material offered is absorbed by the children who study it. For this reason, this study aims to compare how effective public PAUD and private PAUD are in developing IT-based media in PAI PAUD learning in the era of society 5.0. The development of IT-based learning media on PAI learning in South Purwokerto State Kindergarten less effective and Al Fattah Purwokerto Utara IT (Islam Teladan) kindergarten has applied multimedia learning media consisting of computer devices, LCDs and Audio Visual media in KBM effectively.